Relaciones entre los rotíferos, copépodos planctónicos ciclopoides y la calidad del agua en dos embalses Brasileños - Perbiche-Neves, Gilmar; Fileto, Cláudia; Laço-Portinho, Jorge; Troguer, Alysson; Serafim-Júnior, Moacyr (My University, 2013)
Planktonic rotifers and cyclopoid copepods were studied in two reservoirs of different trophic states (eutrophic and oligo/mesoeutrophic) in the south of Brazil. During a year, monthly samplings were carried out in three stations in each reservoir. Species richness, frequency and abundance were used to find out useful and indicatives trends of water quality based on these organisms, reinforced by literature data. Species that showed higher differences between reservoirs were chosen. For Rotifera, richness, frequency and abundance of Brachionus were higher in the eutrophic reservoir, but Plationus patulus occurred only in the oligo/mesotrophic reservoir. For copepods, Tropocyclops prasinus dominated in the eutrophic reservoir, but Thermocyclops decipiens, T. minutus, T. inversus and Microcyclops anceps were dominants in the oligo/mesotrophic reservoir. In the canonical correspondence analysis, these species were indicators of the trophic state and were related with chlorophyll-a, total phytoplankton and total phosphorus. The use of these species can be efficient in the studied regions (subtropical/temperate), but comparing with other Brazilian reservoirs of tropical climate, the results could be different. Despite the dominance of T. decipiens over T. minutus, T. inversus has been widely used in Brazil as an indicator of eutrophic waters; in those cases of excessive eutrophication, other species, more rustic, commonly dominate. In the present study, Thermocyclops was dominant in the oligo/mesotrophic reservoir. The dominance of Brachionus for rotifers and Tropocyclops prasinus and Acanthocyclops robustus for copepods were indicative of eutrophic conditions.
Relations among planktonic rotifers, cyclopoid copepods, and water quality in two Brazilian reservoirs
Keywords: Abundance; Bioindicators; Brazil; Diversity; Evenness; Species richness